ANALISIS PROBLEMATIKA PENERAPAN KURIKULUM MERDEKA BELAJAR PADA SEKOLAH DASAR GUGUS 1 DI KECAMATAN SELAPARANG KOTA MATARAM - Nurwahdania, Nurwahdania; Karma, I Nyoman; Syazali, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe teacher problems in implementing the Independent Learning Curriculum at Cluster 1 Elementary Schools in Selaparang District, Mataram City. The type of research used is descriptive research using a qualitative approach. The subjects in this research were class teachers who implemented the Merdeka Curriculum in each school at SD Gugus 1, Selaparang District, Mataram City. Data collection was carried out using interview techniques, questionnaires and documentation. The data analysis techniques used are data collection, data reduction, data presentation, conclusions and verification. Meanwhile, data validity testing was carried out using technical triangulation and source triangulation. The results of the research show that teachers' problems in implementing the Independent Learning Curriculum in planning, implementing and processing assessment/assessment results are difficulties in analyzing or understanding CP and its components, using a constructivist approach in preparing plans, compiling TP and ATP, determining models and approach methods in learning, preparing and developing teaching modules, using teaching modules prepared by the government, implementing differentiated learning, coordinating and organizing students, growing the Pancasila student profile in students, using media and learning resources, determining follow-up for students, lack of references and feedback from parents of students.